The Impact of Job Satisfaction on Teacher Mental Health: A Call to Action for Educational Policymakers - Singh Yogendra Kumar; Gautam Dev Nath Singh (De Gruyter, 2024)
Job satisfaction significantly impacts teachers' overall well-being and mental health. Research reveals a strong connection between employment status and mental health, with teaching being a particularly stressful profession. The COVID-19 pandemic exacerbated these challenges, with the shift to online education and limited support causing heightened stress, anxiety, and depression. This study analyses scientific literature exploring the link between job satisfaction and mental health (depression, stress, and anxiety) in teachers. By examining relevant articles in major databases like Web of Science, PSYNDEX, PsycINFO, MEDLINE, EMBASE, and Google Scholar, the research identifies numerous sociodemographic and institutional factors contributing to teachers' mental health struggles, including workload, teaching experience, job satisfaction, gender, and the nature of online education. The findings highlight the urgent need for educational policymakers to develop policies prioritizing teacher well-being, especially during times of crisis. This involves addressing factors affecting job satisfaction and implementing strategies to promote mental health support for educators.